2013
DOI: 10.1007/s11999-012-2758-9
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Pulmonary Embolism and Deep Vein Thrombosis After Knee Arthroplasty in Asians Remains Low: A Meta-analysis

Abstract: The incidence of symptomatic PE and DVT after TKA without prophylaxis is low in Asian countries and has not changed over time, despite Westernizing lifestyles and an aging populace. Further investigation with large randomized studies is necessary to confirm our findings and identify risk factors predisposing to DVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
96
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 38 publications
5
96
2
Order By: Relevance
“…There were several cases with subsegmental atelectasis; however, no case with clinically significant atelectasis (lobar or whole lung atelectasis evidenced on a chest radiograph or requiring bronchoscopic toileting) was observed. In addition, we did not encounter any case of pulmonary embolism, which is not an unusual finding because the incidence of postoperative pulmonary embolism in Asian countries is far lower than in Western countries [13]. …”
Section: Resultsmentioning
confidence: 99%
“…There were several cases with subsegmental atelectasis; however, no case with clinically significant atelectasis (lobar or whole lung atelectasis evidenced on a chest radiograph or requiring bronchoscopic toileting) was observed. In addition, we did not encounter any case of pulmonary embolism, which is not an unusual finding because the incidence of postoperative pulmonary embolism in Asian countries is far lower than in Western countries [13]. …”
Section: Resultsmentioning
confidence: 99%
“…Venous thromboembolism in Asians has been reported to be low. 30 A recent case-control study confirmed that current exposure to any COC poses a 3-times higher risk of venous thromboembolism compared with no exposure in the previous year. 31 The risk is higher with COC pills containing desogestrel (odds ratio, 4.3), gestodene (3.6), drospirenone (4.1), and cyproterone (4.3) than the second-generation COC pills with levonorgestrel (2.4) and norgestimate (2.5).…”
Section: Discussionmentioning
confidence: 93%
“…In a study by Bin Abd Razak et al, (14) the authors reported that the rate of clinically symptomatic DVT of patients who underwent knee arthroplasty was 0.5%. Low et al (15) reported a 2% incidence of clinically symptomatic DVT, while a meta-analysis by Lee et al (16) showed a 1.9% incidence of symptomatic DVT. Lee et al (16) showed that the incidence of DVT would be as high as 40.4% if asymptomatic DVT was included.…”
Section: Discussionmentioning
confidence: 99%
“…Low et al (15) reported a 2% incidence of clinically symptomatic DVT, while a meta-analysis by Lee et al (16) showed a 1.9% incidence of symptomatic DVT. Lee et al (16) showed that the incidence of DVT would be as high as 40.4% if asymptomatic DVT was included. Thus, we concluded that as our fi ndings are comparable, this study refl ects the actual situation for Asian patients undergoing arthroplasty.…”
Section: Discussionmentioning
confidence: 99%